Comparative ribosome profiling uncovers a dominant role for translational control in Toxoplasma gondii - Hassan, Musa A. (BMC Genomics, 2017)
BACKGROUND: The lytic cycle of the protozoan parasite Toxoplasma gondii, which involves a brief sojourn in the extracellular space, is characterized by defined transcriptional profiles. For an obligate intracellular parasite that is shielded from the cytosolic host immune factors by a parasitophorous vacuole, the brief entry into the extracellular space is likely to exert enormous stress. Due to its role in cellular stress response, we hypothesize that translational control plays an important role in regulating gene expression in Toxoplasma during the lytic cycle. Unlike transcriptional profiles, insights into genome-wide translational profiles of Toxoplasma gondii are lacking. METHODS: We have performed genome-wide ribosome profiling, coupled with high throughput RNA sequencing, in intracellular and extracellular Toxoplasma gondii parasites to investigate translational control during the lytic cycle. RESULTS: Although differences in transcript abundance were mostly mirrored at the translational level, we observed significant differences in the abundance of ribosome footprints between the two parasite stages. Furthermore, our data suggest that mRNA translation in the parasite is potentially regulated by mRNA secondary structure and upstream open reading frames. CONCLUSION: We show that most of the Toxoplasma genes that are dysregulated during the lytic cycle are translationally regulated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-017-4362-6) contains supplementary material, which is available to authorized users.